The acceptance of telehomecare system amongst the elderly with chronic diseases / Nor Afirdaus Zainal Abidin, Mohd Helmy Abd Wahab and Asma Zubaida Mohamed Ibrahim - Zainal Abidin, Nor Afirdaus; Abd Wahab, Mohd Helmy; Mohamed Ibrahim, Asma Zubaida (2022)
Telehomecare system is a technology that enables patients to be monitored at home by health workers. The system involved data collection, knowledge transfer and communication between patients and health workers. Patients, especially the elderly who are suffering from chronic disease such as diabetic, hypertension or heart disease, are the best target users to use the systems. Chronic diseases are the major cause of death and disability in Malaysia, accounted for 71% of all deaths and 69% of the total burden of disease. A semi-structured interview was conducted amongst thirty elderly patients suffering from any one of the chronic diseases. This paper shall propose a framework for integrating medical record between Telehomecare system and health system called the 1THSystem. Patients do not need to go to the hospital for regular treatment. The regular checkup can be monitored at home to enable the elderly health monitoring and management and to ease their daily routine. This can reduce the number of hospital admissions, facilitate more efficient clinical visits, and may replace a hospital stay by living at home.